STUDENTS’ EXPERIENCE WITH ENGLISH PUBLIC SPEAKING - Risal, Laode; Tohamba, Citra Prasiska Puspita; Syarif, Andi Rachmawati (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2024)
This research uses a descriptive qualitative approach involving three participants who are alumni of Universitas Muhammadiyah Kendari, who have completed an international credit transfer (ICT) program at Nueva Ecija University of Science and Technology (NEUST), Philippines, from August to December 2023. This research helps how to improve students' experiential skills in public speaking preparation and satisfaction. Findings show that public speaking helps to overcome fear, increase confidence, and deliver effective speeches. Effective preparation, including message formulation, material organization, presentation techniques, and audience consideration, plays an important role in reducing anxiety and improving speech quality. Ultimately, regular public speaking practice proves instrumental in fostering psychological resilience and language proficiency among students.